Construction of pH-responsive drug delivery platform with calcium carbonate microspheres induced by chitosan gels. Issue 7 (May 2018) - Wang, Jingwei; Kong, Yong; Liu, Feng; Shou, Dan; Tao, Yongxin; Qin, Yong
Abstract: Construction of simple and convenient platforms for controlled delivery of anti-cancer drugs is of great importance for medical science and pharmaceutics. Here, chitosan (CS) gels were used to induce the growth of calcium carbonate (CaCO3 ) microspheres, and the resulting CaCO3 microspheres were well dispersed within the three-dimensional (3D) network framework of the CS gels. The synthesized CaCO3 /CS composites were then examined by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared spectrometry (FT-IR) and X-ray diffractometry (XRD). Finally, the designed CaCO3 /CS composites were used for loading and controlled delivery of methotrexate (MTX), an anti-cancer drug. The encapsulation ratio of MTX calculated by UV–vis spectroscopy was approximately 78.8%. In addition, pH-responsive delivery of MTX from the CaCO3 /CS composites was successfully achieved due to the pH-sensitive property of CS, and the cumulative release of MTX could reach 93.3%, 86.6% and 77.6% at pH 8.5, 7.4 and 5.8, respectively.